Modulation of bone turnover aberration: A target for management of primary osteoporosis in experimental rat model. Issue 2 (February 2020) - Fouad-Elhady, Enas A.; Aglan, Hadeer A.; Hassan, Rasha E.; Ahmed, Hanaa H.; Sabry, Gilane M.
Abstract: Osteoporosis is a skeletal degenerative disease characterised by abnormal bone turnover with scant bone formation and overabundant bone resorption. The present approach was intended to address the potency of nanohydroxyapatite (nHA), chitosan/hydroxyapatite nanocomposites (nCh/HA) and silver/hydroxyapatite nanoparticles (nAg/HA) to modulate bone turnover deviation in primary osteoporosis induced in the experimental model. Characterisation techniques such as TEM, zeta-potential, FT-IR and XRD were used to assess the morphology, the physical as well as the chemical features of the prepared nanostructures. The in vivo experiment was conducted on forty-eight adult female rats, randomised into 6 groups (8 rats/group), (1) gonad-intact, (2) osteoporotic group, (3) osteoporotic + nHA, (4) osteoporotic + nCh/HA, (5) osteoporotic + nAg/HA and (6) osteoporotic + alendronate (ALN). After three months of treatment, serum sclerostin (SOST), bone alkaline phosphatase (BALP) and bone sialoprotein (BSP) levels were quantified using ELISA. Femur bone receptor activator of nuclear factor-kappa B (NF-κB) ligand (RANKL) and cathepsin K (CtsK) mRNA levels were evaluated by quantitative RT-PCR. Moreover, alizarin red S staining was applied to determine the mineralisation intensity of femur bone. Findings in the present study indicated that treatment with nHA, nCh/HA or nAg/HA leads to significant repression of serum SOST, BALP and BSP levels parallel to a significant down-regulation of RANKL and CtsK gene expression levels. On the other side, significant enhancement in the calcification intensity of femur bone has been noticed. The outcomes of this experimental setting ascertained the potentiality of nHA, nCh/HA and nAg/HA as promising nanomaterials in attenuating the excessive bone turnover in the primary osteoporotic rat model. The mechanisms behind the efficacy of the investigated nanostructures involved the obstacle of serum and tissue indices of bone resorption besides the strengthening of bone mineralisation. Abstract : Materials science; Nanotechnology; Biomedical engineering; Silver nanoparticles; Nanohydroxyapatite; Chitosan nanoplatform; Bone turnover; Primary osteoporosis